Medicine and paradoxography in the ancient world - Kazantzidis, Georgios, 1979- (Trends in classics. Supplementary volumes, 2019)
The present volume offers a systematic discussion of the complex relationship between medicine and paradoxography in the ancient world. For a long time, the relationship between the two has been assumed to be virtually non-existent. Paradoxography is concerned with disclosing a world full of marvels and wondrous occurrences without providing an answer as to how these phenomena can be explained. Its main aim is to astonish and leave its readers bewildered and confused. By contrast, medicine is committed to the rational explanation of human phusis, which makes it, in a number of significant ways, incompatible with thauma. This volume moves beyond the binary opposition between?rational? and?non-rational? modes of thinking, by focusing on instances in which the paradox is construed with direct reference to established medical sources and beliefs or, inversely, on cases in which medical discourse allows space for wonder and admiration. Its aim is to show that thauma, rather than present a barrier, functions as a concept which effectively allows for the dialogue between medicine and paradoxography in the ancient world.